The Promise of Genetics and Genomics for Improving Invasive Mammal Management on Islands - Burgess, Brock T.; Irvine, Robyn L.; Howald, Gregg R.; Russello, Michael A. (Frontiers in Ecology and Evolution, 2021)
Invasive species are major contributors to global biodiversity decline. Invasive mammalian species (IMS), in particular, have profound negative effects in island systems that contain disproportionally high levels of species richness and endemism. The eradication and control of IMS have become important conservation tools for managing species invasions on islands, yet these management operations are often subject to failure due to knowledge gaps surrounding species- and system-specific characteristics, including invasion pathways and contemporary migration patterns. Here, we synthesize the literature on ways in which genetic and genomic tools have effectively informed IMS management on islands, specifically associated with the development and modification of biosecurity protocols, and the design and implementation of eradication and control programs. In spite of their demonstrated utility, we then explore the challenges that are preventing genetics and genomics from being implemented more frequently in IMS management operations from both academic and non-academic perspectives, and suggest possible solutions for breaking down these barriers. Finally, we discuss the potential application of genome editing to the future management of invasive species on islands, including the current state of the field and why islands may be effective targets for this emerging technology.